Opinion and Reform in Hume's Political Philosophy. - Stewart, John B. (Princeton legacy library., 2014)
""The picture of Hume clinging timidly to a raft of custom and artifice, because, poor skeptic, he has no alternative, is wrong, "" writes John Stewart. ""Hume was confident that by experience and reflection philosophers can achieve true principles."" In this revisionary work Stewart surveys all of David Hume's major writings to reveal him as a liberal moral and political philosopher. Against the background of seventeenth-and eighteenth-century history and thought, Hume emerges as a proponent not of conservatism but of reform. Stewart first presents the dilemma over morals in the modern natu